2001
DOI: 10.1142/s021853930100058x
|View full text |Cite
|
Sign up to set email alerts
|

Failure Modes in Medical Device Software: An Analysis of 15 Years of Recall Data

Abstract: Most complex systems today contain software, and systems failures activated by software faults can provide lessons for software development practices and software quality assurance. This paper presents an analysis of software-related failures of medical devices that caused no death or injury but led to recalls by the manufacturers. The analysis categorizes the failures by their symptoms and faults, and discusses methods of preventing and detecting faults in each category. The nature of the faults provides less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(75 citation statements)
references
References 10 publications
1
74
0
Order By: Relevance
“…There is evidence that the increasing complexity of IMD software is already taking a toll on the biomedical industry. From 1983 to 1997, 6% of the recalls issued for medical devices containing software were attributable to software failures [25]. From 1999 to 2005, 11.3% of the recalls were attributable to software failures, a near doubling of the software-related recall rate [2].…”
Section: Hardware Vs Software Security Risksmentioning
confidence: 99%
“…There is evidence that the increasing complexity of IMD software is already taking a toll on the biomedical industry. From 1983 to 1997, 6% of the recalls issued for medical devices containing software were attributable to software failures [25]. From 1999 to 2005, 11.3% of the recalls were attributable to software failures, a near doubling of the software-related recall rate [2].…”
Section: Hardware Vs Software Security Risksmentioning
confidence: 99%
“…Safety is a key area which must be successfully addressed given the potential for harm that defective medical device software can cause. An analysis of medical device recalls by the FDA in 1996 [40] found that software was increasingly responsible for product recalls: In 1996, 10% of product recalls were caused by software-related issues. The standards and guidelines created to overcome this have already been discussed, but problems still persist.…”
Section: X228 Traceability For Medical Device Software Developmentmentioning
confidence: 99%
“…An analysis of medical device recalls by the FDA in 1996 [33] found that software was increasingly responsible for product recalls. This continues to be the case and in the period the 1 st January 2010 to 1 st January 2011 the FDA recorded 80 medical device recalls and state software as the cause [46].…”
Section: Regulatory Nature Of the Medical Device Domainmentioning
confidence: 99%